Treatment of infertile women with unilateral tubal occlusion by intrauterine insemination and ovarian stimulation - Ming-Huei Lin; Yuh-Ming Hwu; Shyr-Yeu Lin; Robert Kuo-Kuang Lee (Elsevier, 2013)
Objective: The aim of this study was to evaluate the value of intrauterine insemination (IUI) combined with ovarian stimulation in women with unilateral tubal occlusion detected on hysterosalpingography (HSG). Materials and Methods: A total of 703 patients undergoing IUI and controlled ovarian hyperstimulation were enrolled in this study. The study group consisted of 133 patients treated for unilateral tubal occlusion diagnosed by HSG during 2005-2011. The control group consisted of 570 patients with unexplained infertility treated during the same period. In all cases of the retrospective study, menstrual cycles were regular, basal serum follicle-stimulating hormone levels and sperm parameters were normal. Results: There were no significant differences in pregnancy rate per cycle between the study (17.3%) and control groups (18.9%). The pregnancy rate was higher in patients with proximal tubal occlusion (21.7%) compared with mid-distal tubal occlusion (12.5%) or unexplained infertility (18.9%), but the difference was not statistically significant. Conclusions: Infertile patients with only unilateral proximal tubal occlusion detected on HSG can be treated initially by IUI combined with ovarian stimulation. The cycle outcomes in patients with proximal tubal occlusion are similar to patients with unexplained infertility. However, the stimulated IUI might not be a good choice for patients with unilateral mid-distal tubal occlusion because of a lower success rate, although further evidence is needed.